Legal Certainty on the Form of Outsourching Work Agreements Based on the Regulation of the Minister of Manpower and Transmigration Number 19 of 2012 concerning Conditions for Submission of Part of the Implementation of Work to Other Companies - Ghina Rahmania; Imam Budi Santoso; Holyness N. Singadimedja (IHSA Institute, 2022)
The falling economic condition has forced the government and business to be more creative in creating business climate, government has created the legal instruments for the development of the investment through business activities. On the other hand, business actors try to catch every single business opportunity available, for example to make efficiency to cut the operational expenses. Outsourcing system becomes the trend used by several companies. Many big companies hire their workers through this system. The problems occurred were the employment of the Regulation of Ministry of Labor and Transmigration No. 19 of 2012 concerning Terms on Distribution of Work Partly to Other Corporation; the legal protection for the oursourcing worker under the Law No. 13 of 2003 concerning Labor jo Regulation of Ministry of Labor and Transmigration No. 19 of 2012 concerning Terms on Distribution of Work Partly to Other Corporation; the settlement to be taken by the government to protect the outsourcing workers. The method of research used in this was descriptive analytical specification in which the researcher described or illustrated a case that was analyzed with the laws using juridical normative method of approach. Stages of research used included library and field research. Data collecting technique was throudocument study and field study in the form of interview. The findings of the research concluded that both has violated Article 17 section (3) of the Regulation of Ministry of Labor and Transmigration No. 19 of 2012 in which both corporations did not place the outsourcing workers in supporting job, instead, they were posted for main job. The protection given by in general was similar namely health insurance, holiday allowance, overtime incentives. While at the other company, they gave one more incentives that was end of contract pension. The judgment of Constitutional Court No. 27/PUU-IX/2011 deciding in favour of the interest of the workers, ordered that every outsourcing worker should have their rights equal to the rights of the non-outsourcing workers. In addition, outsourcing company should count the working time into the guidance to determine the wages and other rights at the outsourcing companies including the transferof from the company receiving other works.